Incidence and outcome of no flow after primary percutaneous coronary intervention in acute myocardial infarction - Goutam Datta; Sandipan Sarkar (The Indonesian Heart Association, 2020)
Background: Mechanical revascularization of the infarct-related artery (IRA) is the most effective treatment modality in ST-segment elevation myocardial infarction (STEMI).No flow occurs in ∼8.8-10% of cases of primary percutaneous coronary intervention(PCI) in STEMI patients. Our aim was to study actual incidence and outcome of no flow patients. Methods: Five hundred and eighty primary PCI patients were studied over a period of two years i.e. January 2016 to December 2017. Drug eluting stents were used in all cases. Majority of our patients(>90%) came 6 hours after onset of chest pain. There were many patients where there was no flow even after mechanical thrombus aspiration and pharmacological vasodilator therapy. We have studied primary outcome(mortality) of no flow in those patients. Results: There were 44 cases of no flow in our series(7.75%). Left anterior descending artery(LAD )was involved in eighteen patients. Right coronary artery(RCA) was culprit in twenty four cases. Only two cases were seen in LCX territory. One month mortality rate in no flow group was 50% and 6.25% in successful recanalization group. One year mortality was 12.5% in successful recanalization group and 66% in no flow group. Conclusion: Refractory no flow during primary PCI in STEMI is associated with high mortality and morbidity. There is no established strategy to solve this phenomenon.